Delayed presentation of acute ischemic strokes during the COVID-19 crisis. (28th May 2020) - Schirmer, Clemens M; Ringer, Andrew J; Arthur, Adam S; Binning, Mandy J; Fox, W Christopher; James, Robert F; Levitt, Michael R; Tawk, Rabih G; Veznedaroglu, Erol; Walker, Melanie; Spiotta, Alejandro M
Abstract : Background: The COVID-19 pandemic has disrupted established care paths worldwide. Patient awareness of the pandemic and executive limitations imposed on public life have changed the perception of when to seek care for acute conditions in some cases. We sought to study whether there is a delay in presentation for acute ischemic stroke patients in the first month of the pandemic in the US. Methods: The interval between last-known-well (LKW) time and presentation of 710 consecutive patients presenting with acute ischemic strokes to 12 stroke centers across the US were extracted from a prospectively maintained quality database. We analyzed the timing and severity of the presentation in the baseline period from February to March 2019 and compared results with the timeframe of February and March 2020. Results: There were 320 patients in the 2-month baseline period in 2019, there was a marked decrease in patients from February to March of 2020 (227 patients in February, and 163 patients in March). There was no difference in the severity of the presentation between groups and no difference in age between the baseline and the COVID period. The mean interval from LKW to the presentation was significantly longer in the COVID period (603±1035 min) compared with the baseline period (442±435 min, P<0.02). Conclusion: We present data supporting an association between public awareness and limitations imposed on public life during the COVID-19 pandemic in the US and a delay in presentation for acute ischemic stroke patients to a stroke center.